Thermodynamic and Kinetic Study of the Reaction Mechanism of Acetylsalicylic Acid Formation Using Computational Chemistry Methods - Julina Indah Gewa Sitompul; Roma Sinaga; Asep Wahyu Nugraha (Universitas Negeri Medan, 2025)
Acetylsalicylic acid or aspirin is one of the most widely used non-steroidal anti-inflammatory drugs (NSAIDs) in medicine because of its properties as an analgesic, antipyretic, and antiplatelet. This study aims to examine the thermodynamic and kinetic aspects of the reaction mechanism of aspirin formation from salicylic acid and acetic anhydride using a computational chemistry approach. The method used to determine energy is the computational chemistry method, the theory used is metode Restricted Hartree-Fock (RHF) with a basis set of 3-21G. The calculation results show the formation of energy (ΔE) of the reaction of -1.21 kJ/mol. The magnitude of the activation energy (Ea) from the computational chemistry calculation is 7.95 kJ/mol. The structure of the intermediate was also successfully identified and visualized, supporting a two-stage reaction mechanism with the presence of a transition state